Retrospective determination of 137Cs specific activity distribution in spruce bark and bark aggregated transfer factor in forests on the scale of the Czech Republic ten years after the Chernobyl accident - Suchara, I; Rulík, P; Hůlka, J; Pilátová, H (The Science of the total environment, 2011)
The (137)Cs specific activities (mean 32Bq kg(-1)) were determined in spruce bark samples that had been collected at 192 sampling plots throughout the Czech Republic in 1995, and were related to the sampling year. The (137)Cs specific activities in spruce bark correlated significantly with the (137)Cs depositions in areas affected by different precipitation sums operating at the time of the Chernobyl fallout in 1986. The ratio of the (137)Cs specific activities in bark and of the (137)Cs deposition levels yielded bark aggregated transfer factor T(ag) about 10.5×10(-3)m(-2)kg(-1). Taking into account the residual specific activities of (137)Cs in bark 20Bq kg(-1) and the available pre-Chernobyl data on the (137)Cs deposition loads on the soil surface in the Czech Republic, the real aggregated transfer factor after and before the Chernobyl fallout proved to be T*(ag)=3.3×10(-3)m(-2)kg(-1) and T**(ag)=4.0×10(-3)m(-2)kg(-1), respectively. The aggregated transfer factors T*(ag) for (137)Cs and spruce bark did not differ significantly in areas unequally affected by the (137)Cs fallout in the Czech Republic in 1986, and the figures for these aggregated transfer factors were very similar to the mean bark T(ag) values published from the extensively affected areas near Chernobyl. The magnitude of the (137)Cs aggregated transfer factors for spruce bark for the pre-Chernobyl and post-Chernobyl period in the Czech Republic was also very similar. The variability in spruce bark acidity caused by the operation of local anthropogenic air pollution sources did not significantly influence the accumulation and retention of (137)Cs in spruce bark. Increasing elevation of the bark sampling plots had a significant effect on raising the remaining (137)Cs specific activities in bark in areas affected by precipitation at the time when the plumes crossed, because the sums of this precipitation increased with elevation (covariable).
Keywords: kinetika; Soil Pollutants, Radioactive; radioizotopy cesia; radioaktivní znečišťující látky; Picea; radioaktivní látky znečišťující půdu; koncentrace vodíkových iontů; Česká republika; kůra rostlin; Czech Republic; Radiation Monitoring; monitorování radiace; černobylská havárie; radioaktivní spad; Chernobyl Nuclear Accident; Cesium Radioisotopes; Hydrogen-Ion Concentration; Kinetics; Plant Bark; Radioactive Fallout; smrk; Radioactive Pollutants